Food Insecurity Is Common in the Orthopedic Trauma Population: A Multicenter Cross-Sectional Study. (14th June 2022) - Leary, Steven; Tully, Zachary; Davison, John; Miller, Aspen; An, Qiang; Glass, Natalie; Kirkpatrick, Tessa; Benda, John; Fitzpatrick, Connor; Fitzpatrick, Daniel; Owen, Erin; Willey, Michael; et al.
Abstract: Objectives: Malnutrition increases the risk for adverse outcomes after musculoskeletal trauma. Food insecurity is an increasingly recognized risk factor for malnutrition. The purpose of this investigation is to evaluate the prevalence and risk factors for food insecurity in a diverse population treated for operative fracture fixation. Methods: A two-center study (Midwest and Pacific Northwest) enrolled participants of any age within 6 months of operative fixation of pelvis or extremity fractures. Food insecurity was assessed using the USDA Household Food Insecurity questionnaire. A score ≥3 indicated food insecurity, 1 or 2 indicated marginal food security, and 0 indicated high food security. Subgroup analysis was performed for participants with available demographic, income, and food access data. Differences between food insecure and food secure participants in continuous and categorical variables were evaluated using the Wilcoxon sum rank test and Fisher's exact test, respectively. Spearman's correlation was used to describe associations between food security scores and participant characteristics. Logistic regression was used to relate patient demographics and odds of food insecurity. Results: Of the 476 participants enrolled, 53 (11%) were food insecure, 48 (10%) had marginal food security, and 375 (79%) were food secure. Those with food insecurity were more commonly female (p < 0.0001). Participants with a household income ≤$15, 000 were 5.7 times more likely to be food insecure (95% CI 1.8–18.1). Widowed/single/divorced participants were 10.2 times more likely to experience food insecurity than married/partnered participants (95% CI 2.3–45.6). Median time to the nearest full-service grocery store was significantly longer for food insecure (t = 10 minutes) than for food secure participants (t = 7 minutes, p = 0.0202). Time to store demonstrated a weak correlation with food security score (r = 0.23, p = 0.0041). Age (r = −0.08, p = 0.327) and hours working (r = −0.10, p = 0.429) demonstrated no correlation with food security score. Conclusions: Food insecurity is common in the musculoskeletal trauma population. Those with lower household incomes and living alone are more likely to experience food insecurity. Food insecurity is a potentially modifiable risk factor for malnutrition-related complications after operative fracture fixation. Funding Sources: None.